Desertification Assessment and Mapping : A Case Study of Turkmenistan, USSR - Kharin, Nikolai G (Annals of Arid Zone, 2016)
The paper deals with desertification study of Turkmenistan arid lands which are vulnerable to such desertification types as degradation of the vegetative cover, wind erosion, water erosion and technogenic desertification. In Turkmenistan. 25% of the territory is not prone to desertification. Metho-dology for preparation of small scale desertification maps by application of space photos has been described and discussed along with criteria of desertification.